IMPROVING PUBLIC SERVICE QUALITY THROUGH THE IMPLEMENTATION OF GOOD GOVERNANCE AT THE SURABAYA CITY REVENUE AGENCY - Andri Purdiono; Ika Devy Pramudiana; Eny Haryati; Sapto Pramono (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
High-quality, effective, efficient, and transparent public services reflect the government's accountability and commitment to meeting societal needs and welfare. However, public service quality often remains a challenge in implementing good governance principles. Therefore, this study aims to evaluate the application of five main principles of good governance—transparency, accountability, participation, responsiveness, and efficiency—to improve the quality of public services at the Surabaya City Revenue Agency. This study uses a qualitative method with a descriptive approach to identify and evaluate the success indicators of these five principles as applied in the agency. Data were collected through observation, interviews, and document analysis related to public services at the Surabaya City Revenue Agency. Results show that transparency in public services has reached 76%, indicating openness of information, though accessibility and completeness of data still need improvement. Accountability stands at 73%, highlighting a need for enhancement in accountability procedures. Community participation is recorded at 68%, indicating the need for increased accessibility and opportunities for public involvement. Responsiveness reaches 70%, which, while adequate, still requires improvements in responsiveness to public needs. Efficiency is at 72%, with a need to simplify procedures to accelerate service delivery. This study concludes that the application of good governance principles at the Surabaya City Revenue Agency is relatively well-implemented but requires improvements in several areas. To enhance public service quality.